2020
DOI: 10.1016/j.nmni.2020.100673
|View full text |Cite
|
Sign up to set email alerts
|

Mutated COVID-19 may foretell a great risk for mankind in the future

Abstract: Coronavirus disease 2019 SARS-CoV-2 (COVID-19) is a zoonotic virus causing a variety of severe respiratory diseases. SARS-CoV-2 is closest to SARS-CoV and MERS-CoV in structure. The high prevalence of COVID-19 is a result of a lack of symptoms at onset. Our study aimed to present an overview of the virus in terms of structure, epidemiology, symptoms, treatment and prevention. Whole genome sequences and some viral proteins were investigated to determine gaps and changes in alternation of nucleotides and amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 16 publications
2
128
0
8
Order By: Relevance
“…This could be attributed to the mutation of the N protein sequence in the coronavirus family. Dawood (2020), reported a moderate mutation of the N-protein of coronaviruses [32]. This is indicative that the SARS-COV-2 virus may have originated from mutations within the family as has been previously suggested [33].…”
Section: Codon Optimization and In Silico Cloningsupporting
confidence: 52%
“…This could be attributed to the mutation of the N protein sequence in the coronavirus family. Dawood (2020), reported a moderate mutation of the N-protein of coronaviruses [32]. This is indicative that the SARS-COV-2 virus may have originated from mutations within the family as has been previously suggested [33].…”
Section: Codon Optimization and In Silico Cloningsupporting
confidence: 52%
“…However, recent research has indicated such factors can affect mortality rates associated with COVID-19 (e.g., (5,19). It may be necessarily to account for such factors as more data becomes available.…”
Section: Seir Compartmental Modelmentioning
confidence: 99%
“…An unimaginably high degree of transmission raised a question of whether evolution was stimulated by mutations. Genetic mutation analysis is essential for understanding evolution [32]. A study was conducted to understand and evaluate the genetic mutations pattern, in which eighty-six genomes of SARS-CoV-2 were selected.…”
Section: Evolution Of Covid-19mentioning
confidence: 99%